Algorytmy rozpoznawania zespołu QRS w sygnałach elektrokardiograficznych pochodzącychod pacjentów z wszczepionym układem stymulującym - Duraj, Agnieszka
This dissertation presents the problem of detection and classification of QRS complexes with ECG signals coming from patients with implanted cardiac pacemaker. Special attention was focused on the use of wavelet - neural networks in above mentioned subject matter of investigation. Efficiency of detection of QRS complex was examined by algorithms working in time domain.
Keywords: detekcja zespołu QRS; sieci falkowo - neuronowe; klasyfikacja rytmu endogennego